Juner New Materials : on the road to IPO - Zhao, Ziqian; McFarlan, F. Warren (Franklin Warren); Xia, Donglin; Jia, Ning ([London] : SAGE, 2016)
Juner had been operating in China's modified plastics material industry for fifteen years and had exhibited strong growth and profitability. However, in 2010, the company's founder and chairman, Xiaomin Chen, began to instigate ambitious future growth plans. This book details Juner's strategies.
Originally Published in: Zhao, Z., McFarlan, F. W., Xia, D., & Jia, N. (2011). Juner New Materials: On the Road to IPO. 3-810-321. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Juner (Firm); Strategic planning -- Case studies; Business planning -- Case studies; Corporations -- Growth -- Case studies